Christian Religious Tolerance in Maintaining Peace in Tangerang Regency - Bahrudin, Memet Isa; Muhlas, Muhlas (Hanifiya: Jurnal Studi Agama-Agama, 2025)
Indonesia's cultural and religious diversity poses significant challenges, particularly in fostering harmony and reducing the risk of racial and religious conflicts, as observed in Panongan District, Tangerang. This study investigates the manifestations of religious tolerance among Christians in Tangerang Regency. Employing a qualitative research approach, the study focuses on understanding societal issues through observation and literature review. The findings reveal that, within the context of Christianity, tolerance is expressed both passively—by accepting differences—and actively—through collaborative efforts. In Panongan District, interfaith tolerance is well-preserved through diverse activities that promote mutual respect and understanding among religious communities. This study concludes that fostering tolerance requires continuous engagement in inclusive practices. Its contribution lies in providing insights into the dynamics of interfaith harmony, offering a model that can be adapted to other multicultural contexts.